2010
DOI: 10.1289/ehp.0901849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spatial Relationships between Health and the Environment: The Rapid Inquiry Facility

Abstract: Background The initiation of environmental public health tracking systems in the United States and the United Kingdom provided an opportunity to advance techniques and tools available for spatial epidemiological analysis integrating both health and environmental data. Objective The Rapid Inquiry Facility (RIF) allows users to calculate adjusted and unadjusted standardized rates and risks. The RIF is embedded in ArcGIS so that further geographical information system (GIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…RIF is embedded in a geographical information system (GIS) that requires ArcGIS and connects to an external database of geocoded health and population data, and is especially useful for spatial analyses around sources of presumed environmental hazards, and in small areas 22 23. With the RIF programme, we produced maps of indirectly standardised disease risks (ie, SMRs) with the Costa Rican population as reference, for men and women separately.…”
Section: Methodsmentioning
confidence: 99%
“…RIF is embedded in a geographical information system (GIS) that requires ArcGIS and connects to an external database of geocoded health and population data, and is especially useful for spatial analyses around sources of presumed environmental hazards, and in small areas 22 23. With the RIF programme, we produced maps of indirectly standardised disease risks (ie, SMRs) with the Costa Rican population as reference, for men and women separately.…”
Section: Methodsmentioning
confidence: 99%
“…Another milestone noted was the introduction of environmental public health indicators, measures, and software tools for assessing health outcomes, exposure, or environmental hazards. 21 Using more refined health-level data, Beale et al 74 and Ball et al 35 demonstrated the utility of using a geographic information system tool (The Rapid Inquiry Facility) for assessing spatial relationships between selected health outcomes and diseases. Aggregated health data, which are supplied by state and local health departments, represent the majority of environmental public health indicators and measures.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the dose may not be a simple function of exposure level multiplied by exposure duration, but rather a function of the frequency of peak exposures above a certain level (impulse exposures). For exposures that vary spatially and with time, geographic information systems and recording subject locations via mobile telephones are being introduced as important tools (Beale et al, 2010).…”
Section: Exposure Assessmentmentioning
confidence: 99%